Autonomy and unmanned vehicles : augmented reactive mission and motion planning architecture /: augmented reactive mission and motion planning architecture. ([2019]) - MahmoudZadeh, Somaiyeh; Powers, David M. W; Zadeh, Reza Bairam
No abstract available